Hazard Rate Estimation Using Varying Kernel Function for Censored Data Type I - Al.Doori et al. (مجلة بغداد للعلوم)
In this research, several estimators concerning the estimation are introduced. These estimators are closely related to the hazard function by using one of the nonparametric methods namely the kernel function for censored data type with varying bandwidth and kernel boundary. Two types of bandwidth are used:  local bandwidth and global bandwidth. Moreover, four types of boundary kernel are used namely: Rectangle, Epanechnikov, Biquadratic and Triquadratic and the proposed function was employed with all kernel functions. Two different simulation techniques are also used for two experiments to compare these estimators. In most of the cases, the results have proved that the local bandwidth is the best for all the types of the kernel boundary functions and suggested that the 2xRectangle and 2xEpanechnikov methods reflect the best results if compared to the other estimators.